Encrypted Data Transmission for secured SMS over Web via EMail Platform (International Journal of Engineering and Computer Science, 2018)
The rapid development of computers andthe way in which technology has been used to supportpersonal needs of users as well as businesses worldwide have been changed by the emergence of the internet. As the Internet becomes a more pervasive part of daily life,people fail to realize that the internet would establish itself as a powerful facilitator of the needs of the common man in such a short period of time. However, an individual’s private information can be disseminated withouthis/her knowledge.Many different types of email security threats exist. The security of an email can be compromised by identity theft, spoofing, imposters and modification of existing messages. Hackers may use all or any of these aforementioned methods to have access into a user's computer.However, the computer architecture that is being used exchange of email are not very reliable and hence, does not provide for much privacy for the users.This undeniable fact is what has prompted the researcher to work on the Secured and Encrypted Data Transmission over the Web in order to protect information exchanged over the internet from being compromised.